Patrones dietéticos y prevención del deterioro cognitivo en adultos mayores. Centro de Salud Julio Moreno. Octubre 2024 – Enero 2025 - Urrea Bustillos, Gerardo Caleb (2025)
Population aging represents an increasing challenge for public health, especially due to the rise in conditions such as cognitive decline among older adults. Nutrition has been shown to play a crucial role in the prevention of such disorders. The general objective is to establish the relationship between dietary patterns and the prevention of cognitive deterioration in older adults attending the Julio Moreno Health Center, in the canton of Guaranda, during the period from October 2024 to January 2025. The adopted methodology had a quantitative approach, correlational type and cross-sectional design. The sample consisted of 31 older adults selected by convenience. Two validated instruments were used: the Mini Nutritional Assessment (MNA) to assess nutritional status and the Mini-Mental State Examination (MMSE) to measure cognitive status. Statistical analysis was conducted using SPSS version 27, employing frequencies, percentages, and Pearson correlation test. Among the most relevant results, it was identified that 64.5% of older adults had no formal education, 51.1% were at risk of malnutrition, and more than 60% showed some degree of cognitive decline. The correlation between nutritional and cognitive status was significant, highlighting that adequate nutrition acts as a protective factor against mental decline. In conclusion, a significant relationship between dietary patterns.